1114 Getting it Right First Time: An Audit of Length of Hospital Stay for Mandibular Fractures. (12th October 2021) - Mitchell, F; Parmar, J
Abstract: Introduction: GIRFT is a Department of Health programme, created to improve efficiency by providing data that gives departments a national standard to encourage reflection and service-improvement. The 2016 document in Oral and Maxillofacial Surgery, suggests the national average length of stay for isolated mandible fractures was 2 days, 1 day pre-operatively and 1 day post-operatively. This Audit aimed to investigate if all admissions in our trust met this standard, as a short stay reduces costs and improves patient experience. Method: Data was collected for all isolated mandibular fracture admissions between January – September 2019, with 89 patients identified. Date of admission, surgery and discharge was recorded which allowed calculation of pre-operative, post-operative, and total stay. Results: 78% of patients had surgery within 24 hours of admission. Admissions on a Saturday were most often delayed, with a mean pre-operative stay of 1.60 days and total stay of 2.55 days. Commonly the reason for delay was not recorded, or due to lack of theatre space. 92% of patients were discharged within 24 hours post-operatively. The average length of stay met the 2-day standard, with Monday admissions having the shortest average stay of 1.45 days. Conclusions: Whilst the majority of patients are treated and discharged within 2 days, improvements and future audit would assist to get closer to the 100% target. Saturday saw the highest number of admissions, which also had the longest average length of stay. A dedicated weekend trauma list would reduce wait times but may be limited by staffing and theatre space.